1996
DOI: 10.1161/01.cir.94.9.2154
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and Risk of Premature Coronary Heart Disease

Abstract: Background Plasma homocysteine levels are modulated by nutritional and genetic factors, among which is the enzyme methylenetetrahydrofolate reductase (MTHFR). A common defective (thermolabile) variant of this enzyme is causally associated with elevated plasma homocysteine, itself an independent risk factor for coronary heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
89
5
4

Year Published

1997
1997
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(108 citation statements)
references
References 23 publications
10
89
5
4
Order By: Relevance
“…There have been reports of increased risk for cardiovascular disease in persons with the MTHFR C677T mutation (Morita et al 1997;Kang et al 1988Kang et al , 1991Gallagher et al 1996;Kluijtmans et al 1996). In one study, the presence of the MTHFR C677T mutation in a group of patients with venous thromboembolic disease in various parts of the body, mainly in deep large veins was examined (Arruda et al 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been reports of increased risk for cardiovascular disease in persons with the MTHFR C677T mutation (Morita et al 1997;Kang et al 1988Kang et al , 1991Gallagher et al 1996;Kluijtmans et al 1996). In one study, the presence of the MTHFR C677T mutation in a group of patients with venous thromboembolic disease in various parts of the body, mainly in deep large veins was examined (Arruda et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…A number of investigations have been done to identify whether the thermolabile mutant, MTHFR C677T causes an increased risk for cardiovascular disease. Some results suggest such a correlation (Morita et al 1997;Kang et al 1988Kang et al , 1991Gallagher et al 1996;Kluijtmans et al 1996), whereas others do not (Verhoef et al 1997;Anderson et al 1997;Ma et al 1996;Deloughery et al 1996;van Bockxmeer et al 1997;Christensen et al 1997;Wilcken et al 1996;Adams et al 1996;Brugada & Marian;1997). Arruda et al have shown that there is a correlation between homozygosity for the MTHFR C677T mutation and venous thromboembolic disease (Arruda et al 1997).…”
mentioning
confidence: 99%
“…12 Recent studies have investigated this mutation as a genetic risk factor for spina bifida [13][14][15] and cardiovascular disease. [16][17][18][19][20] All studies indicate that homozygotes for this transition have mildly elevated plasma homocysteine, especially in circumstances of low folate status 21,22 In this report, we describe the identification of two missense and two nonsense mutations in the MTHFR gene in four unrelated families from Turkish/Greek ancestry with severe MTHFR deficiency. Furthermore, our data contribute to the genotype/phenotype correlations in this metabolic disease.…”
Section: Introductionmentioning
confidence: 89%
“…Indeed, the C677T mutation of the MTHFR gene is not unequivocally associated with increased cardiovascular risk. Some studies support the concept that C677T polymorphism in the MTHFR gene increases the risk (Gallagher et al, 1996;Kluijtmans et al, 1996;Ou et al, 1998) but others do not (Adams et al, 1996;Ma et al, 1996;Schmitz et al, 1996;Verhoef et al, 1997a;Wilcken et al, 1996). Nevertheless, the homozygote mutant genotype leads to hyperhomocysteinemia only when plasma folate status is low in healthy subjects and in patients with cardiovascular disease, thus subjects with this MTHFR mutation may be sensitive to low folate intake (Christensen et al, 1996; Verhoef et al, 1997a).…”
Section: Genetic And/or Nutritional Factor-mediated Hyperhomocysteinementioning
confidence: 99%